FRI0405 Extraarticular Manifestations in Patients with Spondyloarthritis under Biologic Treatment. (15th July 2016) - Pieren, A.; Peiteado, D.; de Miguel, E.; Espinel, M.; Moral, E.; Monjo, I.; Paredes, M.B.; Tornero, C.; Bonilla, G.; Plasencia, C.; Nuño, L.; Villalba, A.; et al.
Abstract : Background: The spondyloarthritides are a heterogeneous group of interrelated and overlapping chronic inflammatory arthropathies. The increasingly use of DMARDs and biologic treatments has led to a change in the profile of the spondyloarthritis patients as well as in the extraarticular manifestations. Objectives: Analyze the extraarticular involvement in patients with Spondyloarthritis under biologic therapy. Methods: A retrospective observational study was conducted in all the patients diagnosed of spondyloarthritis under biologic treatment in our Day-Care Hospital. We analyzed socialdemographic, serological (HLA-B27, ASCAS, IgA, urate levels), clinical aspects and extraarticular manifestations such as cardiological, mucocutaneous, pulmonary, ophthalmological and renal involvement. The association between subgroup diseases, risk factors and extraarticular manifestations was performed with linear regression analysis SPSS. Results: 394 patients were analyzed. 58.8% were male with median age 51 years. We included 173 (43.96%) Ankylosing Spondylitis (AS), 71 (18.2%) non radiographic spondyloartritis (axial and peripheral Spa), 25 (6.35%) Spondyloarthritis associated with inflammatory bowel disease (IBD), 102 (25.9%) Psoriatic Arthritis (PsA), 18 (4.57%) juvenile idiopathic arthritis (JIA) and 5 (1.27%) reactive arthritis. All the patients had received at least one Anti TNF drug and 31.2%, more than one. Infliximab (38.1%) was the most employed drug, followed by Etanercept (31.2%). 69.6% were HLA-B27 positive and 10.4% had high IgA levels. 57.6% presented extraarticular manifestations. By subgroups, the extraarticular involvement was up to 48% in AS, 19.7% in Spa and 27.8% in JIA. Excluding the mucocutaneous and digestive symptoms, we found nonarticular activity in 31.4% PsA and 31.1% IBD. (See Table bellow). 12.4% had uveitis. Despite the biologic therapy, 6% had ophthalmological flares, 1/3 of which was under optimization strategy. The mucocutaneous involvement was shaped as psoriasis (nail, plaque, inverse and pustular psoriasis), erythema multiforme and erythema nodosum. Only one patient developed psoriasis during treatment. The most common nephrologic manifestations was hematuria (58.9%). 9.6% presented hyperuricemia which incidence was higher in AS than in PsA (55.3% Vs 34.2%). Only 8% of those patients had renal insufficiency. Finally, we would like to highlight the development of cancer in 11 patients (2.79%). 5 patients presented renal cancer (1.27% being all of them diagnosed of HLA-B27 positive AS with axial involvement. The risk factors statistically associated with the extraarticular activity found were the positivity of HLA-B27 and the hyperuricemia (p=0.000, p<0.002). We found no correlation with age, sex and hyperIgA. In the development of uveitis, only the HLA-B27 positive was significantly associated. Conclusions: We observed a high prevalence of extraarticular manifestations in our sample of patients with Spondyloarthritis under biologic treatment. Nonetheless, the presence of serious manifestations was still low. The hyperuricemia, cutaneous psoriasis and anterior uveitis were the most frequent extraarticular manifestations. The risk factors associated were HLA-B27 positive and the high levels of urate. Disclosure of Interest: None declared